Molecular sieve SSZ-91, method for preparing SSZ-91, and use of SSZ-91

The introduction of SSZ-91 molecular sieves addresses the need for ZSM-48 materials with reduced hydrogenolysis and disorder, achieving improved catalytic performance and selectivity through its unique structural properties.

JP7671877B2Active Publication Date: 2025-05-02CHEVRON USA INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024002628
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-08-27
Filing Date
2024-01-11
Publication Date
2025-05-02
Estimated Expiration
2036-08-11

AI Technical Summary

Technical Problem

There is a need for ZSM-48 molecular sieves with lower hydrogenolysis and a lower degree of disorder, as well as a demand for pure or substantially pure phase materials with improved selectivity in hydrocarbon conversion and gas separation applications.

Method used

The development of a new family of crystalline molecular sieves, SSZ-91, which is structurally similar to ZSM-48 but with a low defect degree, low aspect ratio, and essentially pure phase composition, thereby inhibiting hydrogenolysis and enhancing catalytic performance.

Benefits of technology

SSZ-91 exhibits a lower degree of hydrogenolysis and improved catalytic performance compared to conventional ZSM-48 materials, with enhanced selectivity and reduced gas production, making it suitable for hydrocarbon conversion and gas separation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671877000017
    Figure 0007671877000017
  • Figure 0007671877000018
    Figure 0007671877000018
  • Figure 0007671877000019
    Figure 0007671877000019
Patent Text Reader

Abstract

To provide a family of new crystalline molecular sieves designated as SSZ-91, a method for making SSZ-91 and use of SSZ-91.SOLUTION: A molecular sieve SSZ-91 is structurally similar to sieves belonging to molecular sieves of a ZSM-48 family, and is characterized as: (1) having a low degree of defects, (2) having a low aspect ratio that inhibits hydrocracking as compared to conventional ZSM-48 materials having an aspect ratio of greater than 8, and (3) being substantially pure phase.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application is related to U.S. patent application Ser. Nos. 14 / 837,071, 14 / 837,087, 14 / 837,108, and 14 / 837,094, all of which were filed on Aug. 27, 2015, and are hereby incorporated in their entireties.

[0002] Described herein is a new family of crystalline molecular sieves designated SSZ-91, methods for preparing SSZ-91, and uses of SSZ-91. [Background technology]

[0003] Crystalline molecular sieves and molecular sieves are particularly useful in applications such as hydrocarbon conversion, gas drying and separation due to their unique sieving properties as well as their catalytic properties. Although many different crystalline molecular sieves have been disclosed, there is a continuing need for new molecular sieves with desirable properties for gas separation and drying, hydrocarbon and chemical conversion, and other applications. The new molecular sieves contain novel internal pore structures and can provide improved selectivity in these processes.

[0004] Molecular sieves have distinct crystal structures, revealed by distinct X-ray diffraction patterns, that define cavities and pores characteristic of the different species.

[0005] Molecular sieves are classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature. Framework-type zeolites and other crystalline microporous molecular sieves whose structures have been established according to this classification are assigned three-letter codes and are described in the "Atlas of Zeolite Framework Types", 6th Revised Edition, Elsevier (2007), and in the database of molecular sieve structures on the International Zeolite Association website (http: / / www.iza-online.org).

[0006] The structure of a molecular sieve can be ordered or disordered. A molecular sieve with an ordered structure has periodic building blocks (PerBUs) that are periodically ordered in all three dimensions. A structurally disordered structure exhibits periodic ordering in less than three dimensions (i.e., in 2, 1, or 0 dimensions). Disorder occurs when PerBUs connect in different ways or when two or more types of PerBUs intergrow within the same crystal. A crystal structure created from PerBUs is called an end-member structure when periodic ordering is achieved in all three dimensions.

[0007] In disordered materials, planar stacking faults occur when the material contains two-dimensional ordering. Planar defects disrupt the channels formed by the pore system of the material. Planar defects located near the surface limit the diffusion paths that would otherwise be necessary to allow feedstock components to access the catalytically active portions of the pore system. Thus, as the degree of defects increases, the catalytic activity of the material typically decreases.

[0008] For crystals with planar defects, interpretation of X-ray diffraction patterns requires the ability to simulate the effects of stacking disorder. DIFFaX is a computer program based on a mathematical model for calculating intensities from crystals containing planar defects. (See MMJ Treacy et al., Proceedings of the Royal Chemical Society, London, A (1991), Vol. 433, pp. 499-520). DIFFaX is a simulation program selected by and available from the International Zeolite Society for simulating XRD powder patterns for intergrown phases of molecular sieves. (See Collection of Simulated XRD Powder Patterns for Zeolites, MMJ Treacy and JB Higgins, 2001, 4th Edition, published for the Structure Committee of the International Zeolite Society). DIFFaX has also been used to theoretically study the intergrown phases of AEI, CHA and KFI molecular sieves as reported by KP Lillerud et al. in Studies in Surface Science and Catalysis, 1994, Vol. 84, pp. 543-550. DIFFaX is a well-known and established method for characterizing disordered crystalline materials with planar defects, such as intergrown molecular sieves.

[0009] The symbol ZSM-48 represents a family of disordered materials, each characterized as having a one-dimensional 10-ring tubular pore system. The pores are formed from rolled-up honeycomb-like sheets of condensed tetrahedral 6-ring structures, with the pore openings containing 10 tetrahedral atoms. Zeolites EU-2, ZSM-30 and EU-11 are classified as zeolites of the ZSM-48 family.

[0010] According to Lobo and Koningsveld, the ZSM-48 family of molecular sieves consists of nine polytypes. (See J. Am. Chem. Soc. 2002, 124, 13222-13230). These materials have very similar, but not identical, X-ray diffraction patterns. Lobo and Koningsveld's paper describes their analysis of three ZSM-48 samples provided by Dr. Alexander Kuperman of Chevron Corporation. Each of the three samples, labeled Samples A, B, and C, respectively, was prepared using three different structure directing agents. Comparative Examples 2 and 3 herein below correspond to Samples A and B described in the Lobo and Koningsveld paper.

[0011] The Lobo and Koningsveld paper describes sample A as polytype 6 and sample B as defective polytype 6. The paper further describes the morphology of sample A as consisting of needle-like crystals having a diameter of about 20 nm and a length of about 0.5 μm. The morphology of sample B consisted of long, thin crystals having a width of about 0.5 μm and a length of 4-8 μm. Scanning electron microscope images for samples A and B are shown herein in Figures 3 and 4, as shown in Comparative Examples 2 and 3 below.

[0012] Kirschhock and coworkers have described the successful synthesis of phase-pure polytype 6. (See Chem. Mater. 2009, 21, 371-380.) In their paper, Kirschhock and coworkers report that their phase-pure polytype 6 material, which they call COK-8, has a morphology consisting of long, needle-like crystals (15-80 nm wide; 0.5-4 μm long) with very large length / width ratios that grow along the direction of interconnecting pores.

[0013] As shown in the Kirschhock paper, molecular sieves from the ZSM-48 family of molecular sieves consist of a 10-membered ring, one-dimensional pore structure, in which the channels formed by the interconnected pores run perpendicular to the long axis of the needles. Thus, the channel openings are located at the short ends of the needles. As the length-to-diameter ratio (also known as the aspect ratio) of these needles increases, the diffusion paths for the hydrocarbon feed also increase. As the diffusion paths increase, the residence time of the feed in the channels also increases. Longer residence times result in increased undesirable hydrocracking of the feed, with a concomitant decrease in selectivity. Summary of the Invention [Problem to be solved by the invention]

[0014] Thus, there is currently a need for ZSM-48 molecular sieves that exhibit a lower degree of hydrocracking than known ZSM-48 molecular sieves, and there is a continuing need for ZSM-48 molecular sieves that are phase pure or substantially phase pure and have a low degree of disorder (low degree of defects) in their structure. [Means for solving the problem]

[0015] Described below herein is a family of crystalline molecular sieves having unique properties, referred to herein as "molecular sieve SSZ-91" or simply "SSZ-91". Molecular sieve SSZ-91 is structurally similar to sieves in the ZSM-48 family of zeolites and is characterized by: (1) a low degree of defects, (2) a low aspect ratio that inhibits hydrocracking compared to conventional ZSM-48 materials having aspect ratios greater than 8, and (3) being substantially phase pure.

[0016] As shown in the examples below, ZSM-48 materials lacking any one of the unique combination of three properties of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 composition) exhibit poor catalytic performance.

[0017] In one embodiment, there is provided a molecular sieve having a molar ratio of silicon oxide to aluminum oxide of 40 to 200. In its as-prepared form, the X-ray diffraction lineshape of Table 2 herein is indicative of SSZ-91.

[0018] As determined by DIFFaX simulations and as described by Lobo and Koningsveld in J. Am. Chem. Soc. 2012, 124, 13222-13230 (where disorder is regulated by three different defect probabilities), the SSZ-91 material is composed of at least 70% polytype 6 of the total ZSM-48 type material present in the product. It should be noted that the phrase "at least 70%" includes the case where there are no other ZSM-48 polytypes present in the structure, i.e., the material is 100% phase pure polytype 6.

[0019] In another embodiment, the SSZ-91 is substantially phase pure. The SSZ-91 contains an additional EUO type molecular sieve phase in an amount between 0 and 3.5% (inclusive) by weight of the total product.

[0020] The molecular sieve SSZ-91 has a morphology characterized as polycrystalline aggregates, each of which is characterized as being composed of crystallites collectively having an average aspect ratio between 1 and 8 (inclusive). SSZ-91 exhibits a lower degree of hydrocracking than the ZSM-48 material, which has a higher aspect ratio. An aspect ratio of 1 is the ideal minimum, where the length and width are the same.

[0021] In another aspect, there is provided a method of preparing a crystalline material by contacting, under crystallization conditions, (1) at least one source of silicon oxide; (2) at least one source of aluminum oxide; (3) at least one source of an element selected from Groups 1 and 2 of the Periodic Table; (4) hydroxide ions; and (5) hexamethonium cations.

[0022] In yet another aspect, there is provided a method for preparing a crystalline material having the X-ray diffraction lineshape of Table 2 in an as-produced state, comprising the steps of: (a) providing a reaction mixture containing: (1) at least one source of silicon oxide; (2) at least one source of aluminum oxide; (3) at least one source of an element selected from Groups 1 and 2 of the Periodic Table; (4) hydroxide ions; (5) hexamethonium cations; and (6) water; (b) maintaining the reaction mixture under crystallization conditions sufficient to form crystals of the molecular sieve; The above method is provided by: [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 shows the powder X-ray diffraction (XRD) pattern of the as-synthesized molecular sieve prepared in Comparative Example 1.

[0024] [Diagram 2] 1 is a scanning electron micrograph of the as-synthesized molecular sieve prepared in Comparative Example 1.

[0025] [Diagram 3] 1 is a scanning electron micrograph of the as-synthesized molecular sieve prepared in Comparative Example 2.

[0026] [Figure 4] 1 is a scanning electron micrograph of the as-synthesized molecular sieve prepared in Comparative Example 3.

[0027] [Diagram 5] FIG. 1 shows the powder XRD pattern of the as-synthesized molecular sieve SSZ-91 prepared in Example 7.

[0028] [Figure 6]1 is a scanning electron micrograph of the as-synthesized molecular sieve SSZ-91 prepared in Example 7.

[0029] [Figure 7] 1 is a scanning electron micrograph of the as-synthesized molecular sieve prepared in Example 8.

[0030] [Figure 8] FIG. 1 shows plots of several simulated XRD patterns generated by DIFFaX and the powder XRD pattern of the as-synthesized molecular sieve SSZ-91 prepared in Example 8.

[0031] [Figure 9] FIG. 1 shows plots of several simulated XRD patterns generated by DIFFaX and the powder XRD pattern of the as-synthesized molecular sieve prepared in Example 11.

[0032] [Figure 10] FIG. 1 shows plots of several simulated XRD patterns generated by DIFFaX and the powder XRD pattern of the as-synthesized molecular sieve prepared in Comparative Example 1.

[0033] [Figure 11] 1 is a scanning electron micrograph of the as-synthesized molecular sieve prepared in Example 13.

[0034] [Figure 12] FIG. 1 shows plots of several simulated XRD patterns generated by DIFFaX and the powder XRD pattern of the as-synthesized molecular sieve prepared in Example 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] introduction The term "active source" refers to a reagent or precursor material capable of providing at least one element in a form capable of reacting and being incorporated into the molecular sieve structure. The terms "source" and "active source" may be used interchangeably herein.

[0036] The terms "molecular sieve" and "zeolite" are synonymous and include (a) intermediate and (b) final or end molecular sieves and molecular sieves produced by (1) direct synthesis or (2) post-crystallization treatment (secondary modification). Secondary synthesis techniques allow the synthesis of end materials from intermediate materials by heteroatom lattice substitution or other techniques. For example, aluminosilicates can be synthesized from intermediate borosilicates by post-crystallization heteroatom lattice substitution of B to Al. Such techniques are known, for example, as described in U.S. Patent No. 6,790,433, issued Sep. 14, 2004 to CY Chen and Stacey Zones.

[0037] " * The terms "MRE type molecular sieve" and "EUO type molecular sieve" include all molecular sieves and their isotypes assigned to the International Zeolite Association frameworks as described in "Atlas of Zeolite Framework Types", edited by Ch. Baerlocher, L.B. McCusker and D.H. Olson, Elsevier, 6th Revised Edition, 2007, and the database of zeolite structures on the International Zeolite Association website (http: / / www.iza-online.org).

[0038] The term "Periodic Table" refers to the version of the IUPAC Periodic Table of the Elements dated June 22, 2007, where the numbering system for the Groups of the Periodic Table is as set forth in Chem. Eng. News, 63(5), 26-27 (1985).

[0039] For the purposes of this specification and the appended claims, unless otherwise indicated, all numerical values ​​expressing quantities, percentages or ratios and other numerical values ​​used in the specification and the appended claims are understood to be modified in all instances by the term "about". Thus, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximate and may vary depending on the desired properties sought to be obtained. It should be noted that, as used in this specification and the appended claims, the singular forms "a", "an" and "the" include plural references unless specifically and clearly limited to one referent. As used herein, the term "include" and grammatical variations thereof are open-ended, and thus the enumeration of items in a list does not exclude other similar items that may be substituted for or added to the listed items. As used herein, the term "comprising" means that the term includes the elements or steps identified following it, but that any such elements or steps are not exhaustive and that certain embodiments may include other elements or steps.

[0040] Unless otherwise specified, the recitation of a type of element, material, or other component from which individual components or mixtures of components may be selected is intended to include all possible subgeneric combinations of the listed components and mixtures thereof. Additionally, all numerical ranges presented herein are inclusive of their upper and lower limits.

[0041] The patentable scope is defined by the claims and may include other embodiments that occur to those skilled in the art. Such other embodiments are within the scope of the claims if they have structural elements that do not differ from the literal meaning of the claims, or if they contain equivalent structural elements that have only minor differences from the literal meaning of the claims. Unless inconsistent with this specification, all citations referenced herein are incorporated herein by reference.

[0042] Reaction mixture and crystallization In the preparation of SSZ-91, at least one organic compound selected for synthesis of molecular sieves from the ZSM-48 family of zeolites is used as a structure directing agent ("SDA"), also known as a crystallization template. SDA useful for producing SSZ-91 has the following structure (1): [ka] It is represented by:

[0043] The SDA cation is typically accompanied by an anion, which may be any anion that is not detrimental to the formation of the molecular sieve. Representative examples of anions include hydroxide, acetate, sulfate, carboxylate, and halide ions, such as fluoride, chloride, bromide, and iodide. In one embodiment, the anion is bromide.

[0044] In general, SSZ-91 is: (a) preparing a reaction mixture containing: (1) at least one source of silicon oxide; (2) at least one source of aluminum oxide; (3) at least one source of an element selected from Groups 1 and 2 of the Periodic Table; (4) hydroxide ions; (5) hexamethonium cations; and (6) water; (b) maintaining the reaction mixture under crystallization conditions sufficient to form crystals of the molecular sieve; It is prepared by

[0045] The composition of the reaction mixture from which the molecular sieve is formed is specified in Table 1 below, in terms of molar ratios. [Table 1] In the table, (1) M is selected from the group consisting of elements from Groups 1 and 2 of the Periodic Table; (2) Q is a structure directing agent represented by Structure 1 above.

[0046] Sources useful herein for silicon include fumed silica, precipitated silica, silica hydrogel, silicic acid, colloidal silica, tetra-alkyl orthosilicate (eg, tetraethyl orthosilicate), and silica hydroxide.

[0047] Sources useful herein for aluminum include aluminates, alumina, and AlCl. 3 , Al 2 (SO 4 ) 3 , Al(OH) 3 Examples of sources of aluminum oxide include aluminum compounds such as kaolin clay, as well as other zeolites. One example of a source of aluminum oxide is LZ-210 zeolite, a type of Y zeolite.

[0048] As described hereinabove, for each embodiment described herein, a reaction mixture may be formed containing at least one source of an element selected from Groups 1 and 2 of the Periodic Table (referred to herein as M). In one subembodiment, the reaction mixture is formed with a source of an element from Group 1 of the Periodic Table. In another subembodiment, the reaction mixture is formed with a source of sodium (Na). Any M-containing compound that is not detrimental to the crystallization process is suitable. Sources for such Groups 1 and 2 elements include their oxides, hydroxides, nitrates, sulfates, halides, oxalates, citrates, and acetates.

[0049] For each embodiment described herein, the molecular sieve reaction mixture may be provided by more than one source, and similarly, more than one reactant may be provided by a single source.

[0050] The reaction mixture can be prepared batchwise or continuously. The crystal size, morphology and crystallization time of the molecular sieves described herein can vary depending on the nature of the reaction mixture and the crystallization conditions.

[0051] The reaction mixture is maintained at an elevated temperature until molecular sieve crystals are formed. In general, zeolite hydrothermal crystallization is usually carried out under pressure, typically in an autoclave at a temperature between 125° C. and 200° C. for over 1 to 18 hours, such that the reaction mixture is subjected to autogenous pressure and optionally stirred.

[0052] As described herein above, SSZ-91 is a substantially phase-pure material. As used herein, the term "substantially phase-pure material" means that the material is completely free of zeolitic phases other than those belonging to the ZSM-48 family of zeolites, or present in amounts that have no measurable effect on the selectivity of the material or impart a drawback to the material. Two common phases that co-crystallize with SSZ-91 are EUO-type molecular sieves such as EU-1, as well as magadiite and kenyaite. These additional phases may be present as separate phases or may intergrow with the phase of SSZ-91. As shown in the examples below, the presence of large amounts of EU-1 in the product is detrimental to the selectivity for hydroisomerization with SSZ-91.

[0053] In one embodiment, the SSZ-91 product contains an additional EUO type molecular sieve phase in an amount between 0 and 3.5 wt.%. In one subembodiment, the SSZ-91 contains between 0.1 and 2 wt.% EU-1. In another subembodiment, the SSZ-91 contains between 0.1 and 1 wt.% EU-1.

[0054] It is known that the ratio of powder XRD peak intensities varies linearly as a function of the weight fraction for any two phases in the mixture: (Iα / Iβ)=(RIRα / RIRβ)*(xα / xβ), where the RIR (reference intensity ratio) parameter can be found in the Powder Diffraction File (PDF) database of the International Center for Diffraction Data (http: / / www.icdd.com / products / ). The weight percentage of the EUO phase is therefore calculated by measuring the ratio between the peak intensities of the EUO phase and the SSZ-91 phase.

[0055] The formation of the total EUO phase is controlled by selecting the optimal hydrogel composition, temperature and crystallization time that minimizes the formation of the EUO phase while maximizing the yield of the SSZ-91 product. The following examples provide guidance on how to vary these process variables to minimize the formation of EU-1. Those skilled in the art of zeolite manufacturing can readily select the process variables necessary to minimize the formation of EU-1, as these variables depend on the size of the production run, available equipment capacity, desired target yield and the acceptable level of EU-1 material in the product.

[0056] During the hydrothermal crystallization step, molecular sieve crystals can nucleate naturally from the reaction mixture. Using molecular sieve crystals as seed material can be advantageous in reducing the time required for complete crystallization to occur. Furthermore, seeding can result in higher purity of the resulting product by promoting nucleation and / or formation of the molecular sieve in preference to any undesired phases. However, it has been found that when seeding is used, the seeds must be very phase pure SSZ-91 to avoid the formation of significant amounts of EUO phase. When used as seeds, the seed crystals are added in an amount between 0.5% and 5% of the weight of the silicon source used in the reaction mixture.

[0057] The formation of magadiite and kenyaite is due to the hexamethonium bromide / SiO 2It is minimized by optimizing the ratio, controlling the hydroxide concentration, and minimizing the concentration of sodium since magadiite and kenyaite are layered sodium silicate compositions. The following examples provide guidance on how changes in gel conditions can be made to minimize the formation of EU-1.

[0058] After the molecular sieve crystals are formed, the solid product is separated from the reaction mixture by standard mechanical separation techniques such as filtration. The crystals are washed with water and then dried to obtain the as-synthesized molecular sieve crystals. The drying step can be carried out at atmospheric pressure or under vacuum.

[0059] Post-crystallization treatment The molecular sieve can be used as synthesized, but is typically thermally treated (calcined). The term "as synthesized" refers to the molecular sieve in its form after crystallization prior to removing the SDA cation. SDA can be removed by thermal treatment (e.g., calcination), preferably in an oxidizing atmosphere (e.g., air, a gas with an oxygen partial pressure greater than 0 kPa) at a temperature readily determinable by one skilled in the art sufficient to remove SDA from the molecular sieve. SDA can also be removed by ozone treatment and photolysis techniques (e.g., exposing the SDA-containing molecular sieve product to light or electromagnetic radiation having a wavelength shorter than visible light under conditions sufficient to selectively remove organic compounds from the molecular sieve), as described in U.S. Pat. No. 6,960,327.

[0060] The molecular sieve may then be calcined in steam, air, or an inert gas at a temperature ranging from 200° C. to 800° C. for a period ranging from 1 to 48 hours, or longer. Typically, the extraframework cations (e.g., Na + ) and replace it with hydrogen, ammonium, or any desired metal ion.

[0061] If the molecular sieve formed is an intermediate molecular sieve, the target molecular sieve can be realized using post-synthesis techniques such as heteroatom lattice replacement techniques. The target molecular sieve (e.g., silicate SSZ-91) can also be realized by removing the heteroatoms from the lattice by known techniques such as acid leaching.

[0062] The molecular sieves produced by the methods disclosed herein can be formed into a wide variety of physical shapes. In general, the molecular sieves can be in the form of powders, granules, or shaped articles such as extrudates having a particle size sufficient to pass through a 2 mesh (Tyler) sieve and be retained on a 400 mesh (Tyler) sieve. When the catalyst is shaped, such as by extrusion with an organic binder, the molecular sieve can be extruded prior to drying, or dried or partially dried and then extruded.

[0063] Molecular sieves can be composited with other materials that are resistant to the temperatures and other conditions used in organic conversion processes. Such matrix materials include active and inactive materials and molecular sieves of synthetic or natural origin, as well as inorganic materials such as clays, silicas and metal oxides. Examples of such materials and the manner in which they can be used are disclosed in U.S. Patents 4,910,006 and 5,316,753.

[0064] The extrudates or particles may then be further loaded with one or more active metals selected from the group consisting of metals of Groups 8 to 10 of the Periodic Table, using techniques such as impregnation or ion exchange, to enhance hydrogenation functionality. As disclosed in U.S. Pat. No. 4,094,821, it may be desirable to simultaneously co-impregnate the modifying metal and one or more metals of Groups 8 to 10. In one embodiment, the at least one active metal is selected from the group consisting of nickel, platinum, palladium, and combinations thereof. After metal loading, the metal loaded extrudates or particles may be calcined in air or inert gas at a temperature between 200° C. and 500° C. In one embodiment, the metal loaded extrudates are calcined in air or inert gas at a temperature between 390° C. and 482° C.

[0065] SSZ-91 is useful in a variety of hydrocarbon conversion reactions such as hydrocracking, dewaxing, olefin isomerization, alkylation and isomerization of aromatics etc. SSZ-91 is also useful as an adsorbent for general separation purposes.

[0066] Characterization of molecular sieves The molecular sieves produced by the methods disclosed herein have an SiO 2 / Al 2 O 3 The SSZ-91 has a SAR of between 70 and 160. In another subembodiment, the SSZ-91 has a SAR of between 80 and 140.

[0067] The SSZ-91 material is composed of at least 70% polytype 6 of the total ZSM-48 type material present in the product as determined by DIFFaX simulations and as described by Lobo and Koningsveld in J.Am.Chem.Soc. 2012, 124, 13222-13230 (wherein the disorder is regulated by three different defect probabilities). It should be noted that the phrase "at least X%" includes the case where there are no other ZSM-48 polytypes present in the structure, i.e., the material is 100% polytype 6. The structure of polytype 6 is as described by Lobo and Koningsveld. (See J.Am.Chem.Soc. 2002, 124, 13222-13230). In one embodiment, the SSZ-91 material is composed of at least 80% polytype 6 of the total ZSM-48 type material present in the product. In another embodiment, the SSZ-91 material is comprised of at least 90% polytype 6 of the total ZSM-48 type material present in the product. The structure of polytype 6 has been classified by the International Zeolite Association Structure Committee as the framework code. * MREs are provided.

[0068] The molecular sieve SSZ-91 has a morphology characterized as polycrystalline aggregates having diameters between about 100 nm and 1.5 μm, each of the aggregates comprising a collection of crystallites collectively having an average aspect ratio between 1 and 8. As used herein, the term diameter refers to the shortest length on the short end of each crystallite under consideration. SSZ-91 exhibits a lower degree of hydrocracking than ZSM-48 materials, which have higher aspect ratios. In one subembodiment, the average aspect ratio is between 1 and 5. In another subembodiment, the average aspect ratio is between 1 and 4. In yet another subembodiment, the average aspect ratio is between 1 and 3.

[0069] Molecular sieves synthesized by the methods disclosed herein can be characterized by their XRD patterns. The powder XRD lineshape in Table 2 is representative of as-synthesized SSZ-91 produced according to the methods described herein. Slight variations in the diffraction pattern may result from variations in the molar ratio of framework species in a particular sample due to changes in lattice constants. Additionally, sufficiently small crystals can affect peak shape and intensity, resulting in significant peak broadening. Slight variations in the diffraction pattern may also result from variations in the organic compounds used in the preparation and from variations in the Si / Al molar ratio from sample to sample. Calcination may also result in slight shifts in the XRD pattern. Despite these slight perturbations, the basic crystal lattice structure remains unchanged. [Table 2]

[0070] The X-ray diffraction pattern lineshapes in Table 3 are representative of calcined SSZ-91 produced according to the methods described herein. [Table 3]

[0071] The powder X-ray diffraction patterns presented herein were collected by standard techniques. α The peak heights and positions (as a function of 2θ, where θ is the Bragg angle) can be read from the relative intensities of the peaks (corrected for background) and d (the interplanar spacing corresponding to the recorded lineshape) can be calculated. EXAMPLES

[0072] The following illustrative examples are non-limiting.

[0073] Overview of the Example The following examples demonstrate that ZSM-48 materials lacking any one of the unique combination of the three properties of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 composition) exhibit poor catalytic performance. Table 4 below summarizes the hydrotreating performance for the various examples outlined below. Only Example 8 (SSZ-91) exhibited superior performance, i.e., superior selectivity and low gas production compared to the other three examples. The remaining materials of the other three examples tested exhibited poor performance, as each lacked at least one of the unique combination of the three properties that define SSZ-91. [Table 4]

[0074] Comparative Example 1 Synthesis of ZSM-48 The products in this example were prepared using available reagents according to the teachings of US Pat. No. 5,075,269, issued Dec. 24, 1991 to Thomas F. Degnan and Ernest W. Valyocsik (Mobil Oil Corp.).

[0075] To a 1 gallon autoclave liner was added 76.51 g NaOH (50%), 846 g deionized water, 124.51 g HI-SIL 233 silica (PPG Industries), and 63 g hexamethonium bromide ("HMB", Sigma Aldrich). After all solids were dissolved, Al was dissolved in 733.52 g deionized water. 2 (SO 4 ) 3 18H 2 O 4.35g and concentrated H 2 SO 4 396 g of aluminum stock solution prepared by dissolving 63 g of SSZ-91 seed crystals from Example 7 was added. Finally, 0.45 g of SSZ-91 seed crystals from Example 7 was added. The mixture was stirred until homogeneous. The composition of the produced aluminosilicate gel had the following molar ratios: [Table 5]

[0076] The liner was transferred to a 1 gallon autoclave, which was heated to 160°C for 8 hours and stirred at 150 rpm at autogenous pressure. After 80 hours, the product was filtered, washed with deionized water, and dried. The resulting solid was determined to be ZSM-48 material by XRD (Figure 1). XRD showed an immeasurable amount of EU-1 present in the product (probably less than 1% EU-1). SEM shows aggregated long needle-like crystals of ZSM-48 crystals with an aspect ratio of 7-12 (Figure 2).

[0077] (Comparative Examples 2 and 3) As noted above, the Lobo and Koningsveld paper describes their analysis of three ZSM-48 samples provided by Dr. Alexander Kuperman of Chevron Corporation. Each of the three samples, Samples A, B, and C, was prepared using three different structure directing agents. Lobo and Koningsveld's paper describes Sample A as polytype 6 and Sample B as defective polytype 6. The paper further describes the morphology of Sample A (FIG. 3) as consisting of thin, needle-like crystals having a diameter of about 20 nm and a length of about 0.5 μm. The morphology of Sample B (FIG. 4) consisted of long, thin crystals having a diameter of about 30 nm and a length of 4-8 μm. Although Dr. Kuperman's material was reported to have a high concentration of polytype 6, the samples are characterized as having an aspect ratio (length / diameter) of 25 for Sample A and an aspect ratio ranging between 133 and 266 for Sample B.

[0078] (Examples 4 to 11) Synthesis of SSZ-91 with various EU-1 concentrations in the product Each of Examples 4 through 11 was prepared by adding NaOH (50%), deionized water, HI-SIL 233 silica (PPG Industries), and hexamethonium bromide (Sigma Aldrich) to an autoclave liner. After all solids had dissolved, 540.6 g of Al was added to the autoclave liner. 2 (SO 4 ) 3 18H 2 O 4.18g and concentrated H 2 SO 4 An aluminum stock solution was added, which was prepared by dissolving 45.58 g of aluminum silicate in water. The mixture was stirred until homogeneous. The molar ratios and heating periods for the aluminosilicate gel are listed in Table 6 below. [Table 6]

[0079] The liner was transferred to an autoclave, which was heated to 160° C. for 8 hours and stirred at 150 rpm at autogenous pressure. After the crystallization period, the product was filtered, washed with deionized water, and dried. The resulting solid was analyzed by XRD to determine the product and the level of EU-1 in the product. Bulk SiO 2 / Al 2 O 3 The molar ratios and EU-1 contents are listed in Table 7 below. [Table 7]

[0080] The products from Examples 1 and 4-11 were analyzed by XRD and SEM. The XRD pattern for Example 7 is shown in Figure 5, which is illustrative of the XRD patterns collected for the remaining Examples 4-11.

[0081] SEM images for Examples 7 and 8 are shown in Figures 6 and 7, respectively, which are illustrative of SEM images for the remaining Examples 4-11. Figures 6 and 7 show that the SSZ-91 material is composed of polycrystalline aggregates, each of which is made up of crystallites, where each crystallite has a characteristic average aspect ratio of less than 8. In contrast, the ZSM-48 materials of Comparative Examples 1-3 (Figures 2-4) contained long needle-like crystals and fibrous morphologies, the presence of which morphologies consistently indicated poor catalytic performance.

[0082] Calcination and ion exchange of molecular sieves The as-synthesized products from Comparative Example 1 and Examples 4-11 were converted to the sodium form by heating at a rate of 1°C / min to 120°C and holding for 120 minutes under an atmosphere of dry air, followed by a second temperature ramp of 1°C / min to 540°C and holding at this temperature for 180 minutes, and finally a third temperature ramp of 1°C / min to 595°C and holding at this temperature for 180 minutes. The samples were finally cooled to below 120°C. Each of these calcined samples was then exchanged to the ammonium form as follows: An amount of ammonium nitrate equal to the mass of the sample to be exchanged was completely dissolved in an amount of deionized water ten times the mass of the sample. The sample was then added to the ammonium nitrate solution and the suspension was sealed in a flask and heated in an oven at 95°C overnight. The flask was removed from the oven and the sample was immediately recovered by filtration. The ammonium exchange procedure was repeated with the recovered sample, washed with copious amounts of deionized water to a conductivity of less than 50 μS / cm, and finally dried in an oven at 95°C for 3 hours.

[0083] Hydrotreating Test Palladium ion exchange was carried out on the ammonium exchanged samples from Examples 1 and 4-11 using tetraamminepalladium(II) nitrate (0.5 wt % Pd). After ion exchange, the samples were dried at 95°C and then calcined in air at 482°C for 3 hours to convert the tetraamminepalladium(II) nitrate to palladium oxide.

[0084] 0.5 g of each of the palladium-exchanged samples from Example 11 was loaded into the center of a 23-inch long, 0.25-inch outer diameter stainless steel reactor tube with alundum loaded upstream of the catalyst for preheating the feed (total pressure 1200 psig; downflow hydrogen rate 160 mL / min (measured at 1 atm, 25° C.); downflow liquid feed rate 1 mL / hr). All materials were first reduced in flowing hydrogen at about 315° C. for 1 hour. Products were analyzed by on-line capillary gas chromatography (GC) every 30 minutes. Raw data from the GC was collected by an automated data collection / processing system, and the hydrocarbon conversion was calculated from the raw data.

[0085] The catalyst was first tested at about 260°C to determine the temperature range for the next set of measurements. The entire temperature range resulted in a wide range of hexadecane conversions, with the maximum conversion just below and exceeding 96%. At least five on-line GC injections were collected at each temperature. The conversion was measured using a 1:1 ratio of hexadecane to other products (iso-nC 16 The yield was defined as the amount of hexadecane reacted to produce nC 16 Yield product expressed as weight percent of products other than iso-C 16 The results are included in Table 8. [Table 8]

[0086] The desired isomerization selectivity at 96% conversion for the preferred materials of this invention is at least 85%. A good balance between isomerization selectivity at 96% conversion and temperature is critical to this invention. The desired temperature at 96% conversion is less than 605°F. The lower the temperature at 96% conversion while still maintaining an isomerization selectivity of at least 85%, the more desirable the catalyst. The best catalyst performance is determined by the synergy between isomerization selectivity at 96% conversion and temperature. High amounts of impurities can lead to high levels of C. 4 -Cracking results in undesirable catalytic cracking with its attendant high gas production, as reflected in Table 8. 4 - Cracking is below 2.0%. Note that the selectivity begins to decrease at 6.82% EU-1 as increasing concentrations of EU-1 promote catalytic cracking.

[0087] Polytype distribution Simulated XRD patterns for ZSM-48 materials having between 70-100% polytype 6 were generated using DIFFaX and compared to XRD patterns collected for the molecular sieve products from Examples 8 and 11. The simulated and product XRD patterns are shown in Figures 8 and 9 herein, respectively. Comparing the product XRD patterns to the simulated patterns shows that the products synthesized in Examples 8 and 11 contain greater than 90% polytype 6.

[0088] Simulated XRD patterns for ZSM-48 material having between 70-100% polytype 6 were generated using DIFFaX and compared to the XRD pattern collected for the molecular sieve product from Comparative Example 1. The simulated and product XRD patterns are shown in Figure 10 herein. Comparing the product XRD pattern to the simulated pattern shows that the product synthesized in Comparative Example 1 contains 80% polytype 6.

[0089] The material synthesized in Comparative Example 1 was subjected to the hexadecane hydrotreating tests outlined above in Examples 4-11. The material from Comparative Example 1 exhibited an isomerization selectivity of 78% at 96% conversion at a temperature of 614° F. As shown in Table 9 below, 4 -The cracking was 2.8%. The isomerization selectivity at 96% conversion for the material of Comparative Example 1, which had only 80% polytype 6 content, was inferior to that reported in Examples 4 through 10 shown in Table 7 above, even though the material of Comparative Example 1 contained an unmeasurable (<1%) amount of EU-1. This indicates that the materials of Comparative Example 1 and Example 11 exhibited two of the three properties of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 content), but the lack of the third property contributed to the poor catalytic performance of the materials. [Table 9]

[0090] (Examples 12-13) Synthesis of SSZ-91 from alternative silica sources The material of Example 12 was prepared by adding NaOH (50%), deionized water, CAB-O-SIL M-5 silica (Cabot Corporation), and hexamethonium bromide (HMB) to an autoclave liner. After all solids had dissolved, anhydrous Riedel de Haen sodium aluminate was added. Finally, a SSZ-91 slurry similar to the slurry from Example 4 was added. The mixture was stirred until homogenous. The composition of the resulting aluminosilicate gel had the following molar ratios: [Table 10]

[0091] The liner was transferred to an autoclave, which was heated to 160° C. for 8 hours and stirred at 150 rpm at autogenous pressure. After 48 hours, the product was filtered, washed with deionized water, and dried. The resulting solid was determined by XRD to be SSZ-91 and to contain 0.30 wt. % EUO. Bulk SiO 2 / Al 2 O 3 The molar ratio was found to be about 102.

[0092] NaOH (50%), deionized water, commercially available NALCO 2327 colloidal silica (40.3% SiO 2 The material of Example 13 was prepared by adding Al2O3, which had been pre-dissolved in some water, and hexamethonium bromide to the autoclave liner. After all the solids had dissolved, 2 (SO 4 ) 3 18H 2 O was added. The mixture was stirred until homogeneous. The composition of the resulting aluminosilicate gel had the following molar ratios: [Table 11]

[0093] The liner was transferred to an autoclave, which was heated to 160° C. for 8 hours and stirred at 150 rpm at autogenous pressure. After 35 hours, the product was filtered, washed with deionized water, and dried. The resulting solid was determined by XRD to be SSZ-91 and to contain 3.16 wt. % EU-1. Bulk SiO 2 / Al 2 O 3 The molar ratio was found to be about 155. The material of Example 13 was analyzed by scanning electron microscopy and an SEM image from that analysis is shown in FIG.

[0094] Hydrotreating Test Palladium loading and catalytic testing was performed on the SSZ-91 materials synthesized in Examples 12 and 13 as described for the above examples. The results of the catalytic testing are shown in Table 12 below. These two examples, prepared by varying the raw materials used, show the versatility of the preparation of SSZ-91. Example 12 showed another good example with a desirable isomerization selectivity of 88% at 96% at a fairly low temperature. Example 13, although phase pure, showed poor catalytic performance, a result of the crystal habit with poor crystal aspect ratio. [Table 12]

[0095] Using DIFFaX, simulated XRD patterns for ZSM-48 material with between 70-100% polytype 6 were generated and compared to the XRD patterns collected for the molecular sieve product from Example 13. The simulated and product XRD patterns are shown in FIG. 12 herein. SEM images from this analysis are shown in FIG. 11. Comparing the product XRD pattern to the simulated pattern, the product synthesized in Comparative Example 1 contains more than 90% polytype 6. This indicates that the material of Example 13 has the requisite low EU-1 content and the desired polytype distribution, but the high aspect ratio contributed to the poor catalytic performance of the material. Example 13 again demonstrates that the lack of any one of the three properties of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 content) contributes to the poor catalytic performance of the material. Furthermore, the present invention includes the following preferred embodiments. (1) A molecular sieve belonging to the ZSM-48 family of zeolites, a molar ratio of silicon oxide to aluminum oxide of 40 to 200; At least 70% polytype 6 of the total ZSM-48 type material present in the product, and Additional EUO type molecular sieve phase in an amount between 0 and 3.5% by weight of the total product. Including, having a morphology characterized as polycrystalline aggregates with crystallites collectively having an average aspect ratio between 1 and 8 The molecular sieve described above. (2) in its as-synthesized form, having an X-ray diffraction pattern substantially as shown in the table below [Table 1] JPEG0007671877000014.jpg94161 (1) A molecular sieve according to the present invention. (3) The molecular sieve according to (1) or (2), having a molar ratio of silicon oxide to aluminum oxide of 70 to 160. (4) The molecular sieve according to any one of (1) to (3), having a molar ratio of silicon oxide to aluminum oxide of 80 to 140. (5) The molecular sieve according to any one of (1) to (4), comprising at least 80% polytype 6 of the total ZSM-48 type material present in the product. (6) The molecular sieve according to any one of (1) to (5), containing between 0.1 and 2% by weight of EU-1. (7) The molecular sieve of any one of (1) to (6), wherein the crystallites collectively have an average aspect ratio between 1 and 5. (8) The molecular sieve according to any one of (1) to (7), comprising at least 90% polytype 6 of the total ZSM-48 type material present in the product. (9) The molecular sieve of any one of (1) to (8), wherein the crystallites collectively have an average aspect ratio between 1 and 3. (10) A method for preparing the molecular sieve of any of (1) to (9), comprising the steps of: preparing a reaction mixture containing at least one silicon source, at least one aluminum source, at least one source of an element selected from Groups 1 and 2 of the Periodic Table, hydroxide ions, hexamethonium cations, and water; and subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve. (11) The molecular sieve has the following molar ratio: [Table 2] JPEG0007671877000015.jpg3485 [wherein M is selected from the group consisting of elements from groups 1 and 2 of the periodic table; Q is a hexamethonium cation] The method according to (10), wherein the compound is prepared from a reaction mixture comprising: (12) The molecular sieve has the following molar ratio: [Table 3] JPEG0007671877000016.jpg3485 [wherein M is selected from the group consisting of elements from groups 1 and 2 of the periodic table; Q is a hexamethonium cation] The method according to (10), wherein the compound is prepared from a reaction mixture comprising: (13) A process for converting hydrocarbons, comprising the step of contacting a hydrocarbon-based feedstock under hydrocarbon conversion conditions with a catalyst comprising a molecular sieve according to any one of (1) to (9). (14) Use of a molecular sieve according to any one of (1) to (9) for converting hydrocarbons under hydrocarbon conversion conditions.

Claims

1. A molecular sieve belonging to the ZSM-48 family of zeolites, a molar ratio of silicon oxide to aluminum oxide of 118 to 200; At least 70% polytype 6 of the total ZSM-48 type material present in the product; and Additional EUO type molecular sieve phase in an amount between 0 and 3.5% by weight of the total product. Including, having a morphology characterized as polycrystalline aggregates with crystallites collectively having an average aspect ratio between 1 and 5. The molecular sieve described above.

2. 10. A method for preparing the molecular sieve of claim 1, comprising the steps of preparing a reaction mixture containing at least one silicon source, at least one aluminum source, at least one source of an element selected from Groups 1 and 2 of the Periodic Table, hydroxide ions, hexamethonium cations, and water; and subjecting the reaction mixture to crystallization conditions sufficient to form molecular sieve crystals.

3. 13. A process for converting hydrocarbons comprising the step of contacting a hydrocarbonaceous feedstock under hydrocarbon conversion conditions with a catalyst comprising the molecular sieve of claim 1.

4. 10. Use of the molecular sieve of claim 1 for converting hydrocarbons under hydrocarbon conversion conditions.

Citation Information

Patent Citations

  • Oxygenation treatment of dewaxing catalysts for high yield dewaxing products

    JP2006502000A

  • Hydrotreating using blended zsm-48 catalysts

    JP2009519129A

  • Multiple molecular sieve catalysts for dewaxing in sour environments

    JP2011507696A

  • Production of high viscosity index lubricating oil stock

    US5075269A